2019
DOI: 10.1038/s41436-018-0345-5
|View full text |Cite|
|
Sign up to set email alerts
|

Biallelic sequence and structural variants in RAX2 are a novel cause for autosomal recessive inherited retinal disease

Abstract: PurposeRAX2 encodes a homeobox-containing transcription factor, in which four monoallelic pathogenic variants have been described in autosomal dominant cone-dominated retinal disease.MethodsExome sequencing in a European cohort with inherited retinal disease (IRD) (n = 2086) was combined with protein structure modeling of RAX2 missense variants, bioinformatics analysis of deletion breakpoints, haplotyping of RAX2 variant c.335dup, and clinical assessment of biallelic RAX2-positive cases and carrier family memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Similarly, EYS gene variants were found to be causative in 51% of a RP cohort from Japan [ 36 ]. This discovery is not unique, as several other parallel studies have revealed similar founder mutations in their target populations, for example, Belgium, RAX2 [ 37 ]; Costa Rica, RPE65 [ 38 ]; Finland, CERKL [ 39 ]; Japan, EYS [ 36 ]; Spain, RP1 [ 40 ] and ABCA4 [ 41 ]; Jewish community in Caucasia, PDE6B [ 42 ]; Pakistan, ABCA4 and NMNAT1 [ 43 ]; Guyana, BBS9 [ 44 ]; and Faroe Islands, MERTK [ 45 ]. The enrichment of these variants, several of which are large structural variants, emphasises the value of population-specific TS panels to target and detect mutations and mutational breakpoints that may be missed by commercial generic gene panel sequencing or even WES.…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 56%
“…Similarly, EYS gene variants were found to be causative in 51% of a RP cohort from Japan [ 36 ]. This discovery is not unique, as several other parallel studies have revealed similar founder mutations in their target populations, for example, Belgium, RAX2 [ 37 ]; Costa Rica, RPE65 [ 38 ]; Finland, CERKL [ 39 ]; Japan, EYS [ 36 ]; Spain, RP1 [ 40 ] and ABCA4 [ 41 ]; Jewish community in Caucasia, PDE6B [ 42 ]; Pakistan, ABCA4 and NMNAT1 [ 43 ]; Guyana, BBS9 [ 44 ]; and Faroe Islands, MERTK [ 45 ]. The enrichment of these variants, several of which are large structural variants, emphasises the value of population-specific TS panels to target and detect mutations and mutational breakpoints that may be missed by commercial generic gene panel sequencing or even WES.…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 56%
“…Recently, Van de Sompele et al 2019identified five human patients from unrelated families carrying homozygous mutations in RAX2, some of which are predicted to generate proteins with little, if any, activity. The patients present nonsyndromic autosomal recessive retinitis pigmentosa, with an onset age from childhood to late adulthood (Van de Sompele et al, 2019). This study indicates that, as in other species, the role of RAX2 in humans is to maintain the health of the retina throughout life.…”
Section: Rax/rx Paralogue Genes In Vertebratesmentioning
confidence: 56%
“…Genetic etiologies of retinal dystrophy causing both autosomal dominant and recessive disease have been described in the literature and include RHO , RP1, BEST1 , GUCY2D, RAX2, and RPE65 [17–19, 2124, 25]. Domain-dependent differences in dominant and recessive disease have been suggested for RP1, but the structural correlation of variants with disease phenotype in the other genes is still a topic of investigation [17–19, 21].…”
Section: Discussionmentioning
confidence: 99%